Design of wireless access point configuration network using packet trace r 6.2 at smp negeri 5 prabumulih with development method network development life cycle (ndlc) - Dedi Haryanto; Rama Kipran (Yayasan Pendidikan Rafisqy Arfadhia, 2023)
The The development of computer networks is very rapid and popular so that many network connections are currently popular both in the scope of LAN, Wan, Man topology. Computer networks are often used to connect communications in an area of schools, offices, homes, using the existing topology, Commonly used to build a network installation, The method used in designing access points using ndlc network development life cycle the method consists of analysis, design , simulation prototype, implementation in implementing access point design. Wireless is wifi that is connected or connected to a network and is connected and connected to a laptop or cellphone that has wifi on. Access point is a tool or device to receive signals from the client to the server. Local area network is a network cable to share data to provide convenience to employees.